BENEFITS OF INCENSE WOOD (STRYRAX SP) AS A TRADITIONAL MEDICINE USED BY THE PEOPLE OF SANGIR VILLAGE, KAYU ARO DISTRICT, KERINCI DISTRICT - Ildha Elmonda (SEMESTA: Journal of Science Education and Teaching, 2022)
The incense tree is one of the native Indonesian trees that has medium to large sizes with a diameter of 20-30 cm and a height of 20 to 30 meters. Has a straight stem with slight branches and reddish skin. Frankincense single leaf arranged in a spiral and oval, round elongated with tapered leaf tips. Incense fruit is round and oval with a rather small size. The brown seeds are wrapped in a thick, hard flesh. The use of incense has been known primarily as a traditional medicinal ingredient in Sangir village, Kayu Aro sub-district, Kerinci district because it is effective in treating various diseases, one of which is measles. The substances contained in incense are cinnamic acid, benzoate acid, styrol, styracin, vanillin, coniferilsinamat, coniferil benzoate and a resin containing benzoresinol.